2013
DOI: 10.1097/aog.0b013e3182a6a4d0
|View full text |Cite
|
Sign up to set email alerts
|

Elective Induction of Labor at Term Compared With Expectant Management

Abstract: OBJECTIVE To test the association of elective induction of labor at term compared with expectant management and maternal and neonatal outcomes. METHODS This was a retrospective cohort study of all deliveries without prior cesarean delivery in California in 2006 using linked hospital discharge and vital statistics data. We compared elective induction at each term gestational age (37–40 weeks) as defined by The Joint Commission with expectant management in vertex, non-anomalous, singleton deliveries. We used m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
151
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(179 citation statements)
references
References 28 publications
20
151
4
Order By: Relevance
“…Non-indicated term IOL was associated with clinically meaningful and statistically significant decreased odds of term perinatal mortality at all weeks of gestation prior to the estimated date of confinement (EDC, or due date). Finally, a recent large retrospective study of Californian women, using the same approach as the Scottish study, found clinically meaningful and statistically significant decreased odds of CD with non-indicated IOL at every week of the term period, including the early term weeks [42]. Hence, the findings of this Italian study are consistent with a growing body of evidence suggesting that non-indicated IOL might be more beneficial than harmful.…”
Section: Amor-ipat Exposed 2 Non-exposedsupporting
confidence: 82%
See 1 more Smart Citation
“…Non-indicated term IOL was associated with clinically meaningful and statistically significant decreased odds of term perinatal mortality at all weeks of gestation prior to the estimated date of confinement (EDC, or due date). Finally, a recent large retrospective study of Californian women, using the same approach as the Scottish study, found clinically meaningful and statistically significant decreased odds of CD with non-indicated IOL at every week of the term period, including the early term weeks [42]. Hence, the findings of this Italian study are consistent with a growing body of evidence suggesting that non-indicated IOL might be more beneficial than harmful.…”
Section: Amor-ipat Exposed 2 Non-exposedsupporting
confidence: 82%
“…Finally, most of the observational studies that compared "non-indicated" IOL to spontaneous labour failed to correctly model the actual impact of ni_IOL on the flow of term pregnancy. Specifically, in deciding to perform a ni_ IOL, the actual choice is between delivery now (by "non-indicated" IOL) and delivery later (by either spontaneous labour, some type of IOL at a later date or pre-labour CS) [41,42,54]. Several recent cohort studies that used the correct modeling found that "non-indicated" IOL, as compared with expectant management to a later gestational age, was associated with lower rates of adverse birth outcomes including CD and term stillbirth [40][41][42]55].…”
Section: Amor-ipat Exposed 2 Non-exposedmentioning
confidence: 99%
“…The incidence rate of shoulder dystocia of 0.8% in 2006-08 is still low compared with an American study, which reported an incidence rate of shoulder dystocia of 1.6% in 2006. 34 Hence, shoulder dystocia may previously have been underreported, an explanation that is further supported by the reduction in peripheral nerve injuries. Recently, many obstetric units in Denmark have focused on the management of shoulder dystocia, resulting in a more thorough diagnosis and training of medical staff.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies that compared women who undergo IOL to those who experience spontaneous labor at the same gestational age found that IOL was associated with increased risk for CD 4,5 . However, physicians can never chose between spontaneous or induced labor at any given gestational age, and results from studies comparing IOL to expectant management are mixed, with some studies demonstrating a decreased rate of CD [6][7][8][9] , and others an increased risk for CD 10 . An unfavorable bishop score at the time of IOL may be associated with an increased risk for CD, 11,12 but the largest studies have been unable to account for this important covariate.…”
Section: Introductionmentioning
confidence: 99%